Affirmative Actions in Post Secondary Education: quantitative and qualitative literature review - Basso-Poletto, Daniela (2020)
Affirmative actions are mechanisms of social inclusion that mobilize several spheres of society. This article examines the scientific production obtained by open access bases in Brazil (national and international) of affirmative action for access to post secondary education, aiming an overview of the theme. This is therefore a broad (quantitative and qualitative) review of the publications of the last ten years, considering three languages (Portuguese, English and Spanish), starting with 1105 articles, from three databases (SciELO, SPELL and ANPAD), which were screened by pre-established criteria, resulting in 119 for integral reading and 96 for the analysis itself. The analysis of the articles was based on 4 categories, which examined affirmative actions in different countries, student performance, historical context of publications and policy evaluation. Production on the theme has increased over the years, however, with some weaknesses such as the concentration of studies on very specific realities. It is necessary to advance in the analysis of the trajectory of affirmative actions to better understand their practical application and to provide more consistent dialogues among the investigated realities.